New approach of microstrip antenna integrated with parasitic element for dual function application - Yon, Hamizan; Abd Rahman, Nurul Huda; Aris, Mohd Aziz; Subahir, Suhaila; Awang, Robi'atun Adayiah (UiTM Press, 2025)
Light Emitting Diode (LED) as parasitic element integrated with microstrip antenna in order to improve gain and enhanced antenna functionality has been studied in this research works. The antenna design has been simulated and developed to resonant at 2.45GHz due to rapid development in this frequency for Wi-Fi application. Simulation works have been done using Computer Simulation Technology (CST) to design the antenna. The FR-4 substrate with permittivity, εr = 4.3 and thickness, h = 1.6mm has been used and the surface mount device (SMD) LED is used to completed the simulation process. The stacked antenna consists of three layers substrate where the LEDs as parasitic are located on the top layer with the parallel connection. The radiating patch has been designed located on the second substrate. Meanwhile, ground plane and feed line are located on the bottom substrate. Simulated and measured results was compared to identify the feasibility of proposed integrated antenna. The simulation results have shown that the antenna works well with the integrated LED giving 4.22dBi gain, -25.16dB return loss and 100MHz bandwidth while 3.35dBi gain, -17.79dB return loss and 90MHz bandwidth design without LED placement. The antenna was measured using Vector network analyzer (VNA) and Anechoic chamber. The result of simulation and measurement shows that antenna potentially provides a new opportunity to introduce multi functionality device.